Implementing the Teams Game Tournament model to improve learning outcomes in sprint running - Aprilliani Kartika Putri; Rasyono Rasyono; Weni Agustina (Universitas Sriwijaya, 2025)
Research Problems: Students often show low interest in sprint running lessons, resulting in poor learning outcomes and limited participation. The implementation of the cooperative learning model, Teams Games Tournament (TGT), is expected to create a more interactive, competitive, and enjoyable learning atmosphere that enhances students’ understanding and performance. Research Objective: This study aims to improve students’ learning outcomes in sprint running athletics through the implementation of the Teams Games Tournament (TGT) cooperative learning model. Method: The research was conducted at SMP Negeri 50 Palembang with eighth-grade students during the even semester of the 2024/2025 academic year. The method used was Classroom Action Research (CAR), carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation, learning outcome tests, and documentation. Results: The application of the TGT model effectively increased students’ active participation and learning outcomes in sprint running lessons. The class average score improved from Cycle I to Cycle II, with most students achieving scores above the Minimum Mastery Criteria. Conclusion: The TGT learning model successfully created a fun, competitive, and cooperative learning environment, proving effective in enhancing athletic learning outcomes. This study contributes to innovation in physical education learning and encourages teachers to adopt game-based cooperative approaches in their teaching practices.